Peningkatan Ekonomi Lokal melalui Pemberdayaan Budaya Grebeg Suro Ponorogo - Muhammad Diaz Supandi; Nur Hidayat; Muhammad Adam Saifurrahman; Hilmi Afthon; Niken Sylvia Puspitasari (Jurnal Syntax Admiration, 2024)
The purpose of this study is to determine the improvement of the local economy in Indonesia, especially in the ponorogo district and the empowerment of the grebeg suro culture with the community's economy. The research method applied in this research is a case study with a focus on improving the local economy through the empowerment of Grebeg Suro culture in Ponorogo. The research approach used involves two main dimensions, namely qualitative and quantitative approaches. The qualitative approach aims to deeply understand the impact of cultural empowerment on the local economy, using in-depth interview methods, participatory observation, and documentation studies related to government policies and cultural empowerment programs. Meanwhile, the quantitative approach is used to statistically measure variables related to the local economy, with data analysis using statistical techniques such as regression analysis and t-test. The results show that the government's efforts in overcoming poverty in the Ponorogo community through economic empowerment, especially in the development of the cultural sector such as the annual Grebeg Suro event, have a positive and relevant impact. Grebeg Suro, as a cultural activity with a series of events, successfully attracts visitors from various regions in Indonesia.